Management of traumatic bone defects: Metaphyseal versus diaphyseal defects. (June 2017) - Blokhuis, Taco J.
Abstract: Although bone defects after trauma appear in different locations and forms, many clinicians have adopted a single strategy to deal with any defect. In this overview, a distinction is made between metaphyseal, or cancellous defects, and diaphyseal, or cortical defects. The treatment goals and background of these two types of defects are discussed in order to describe the difference in strategy and hence the difference in treatment method.